Если a=-√2, то значение выражения
 \frac{( - a {}^{3}) {}^{4} + ( - a {}^{4}) {}^{3} + ( - a {}^{2}) {}^{6} + ( - a) {}^{12} }{( - a {}^{2}) {}^{4} + ( - a {}^{4}) {}^{2} - ( - a {}^{8}) }
равно

1Raffaelka1 1Raffaelka1    2   31.07.2019 16:17    3

Ответы
Nikita200111 Nikita200111  03.10.2020 18:49

Рассмотрим отдельно числитель и знаменатель.

1)\; \; (-a^3)^4+(-a^4)^3+(-a^2)^6+(-a)^{12}=\\\\=(-1\cdot a^3)^4+(-1\cdot a^4)^3+(-1\cdot a^2)^6+(-1\cdot a)^{12}=\\\\=(-1)^4\cdot (a^3)^4+(-1)^3\cdot (a^4)^3+(-1)^6\cdot (a^2)^6+(-1)^{12}\cdot a^{12}=\\\\=+a^{12}-a^{12}+a^{12}+a^{12}=2a^{12}\\\\\\2)\; \; (-a^2)^4+(-a^4)^2-(-a^8)=(-1\cdot a^2)^4+(-1\cdot a^4)^2-(-1\cdot a^8)=\\\\=(-1)^4\cdot a^8+(-1)^2\cdot a^8+a^8=+a^8+a^8+a^8=3a^8

3)\; \; a=-\sqrt2\\\\\frac{2a^{12}}{3a^8}=\frac{2}{3}\cdot a^{12-8}=\frac{2}{3}\cdot a^4=\frac{2}{3}\cdot (-\sqrt2)^4=\frac{2}{3}\cdot (-1)^4\cdot (\sqrt2)^4=\frac{2}{3}\cdot 4=\\\\=\frac{8}{3}=2\frac{2}{3}

P.S.\; \; \; 2^*)\; \; (-a^2)^4+(-a^4)^2-(-a)^8=+a^8+a^8-(-1)^8\cdot a^8=\\\\=2a^8-a^8=a^8\\\\3^*)\; \; \frac{2a^{12}}{a^8}=2a^4=2\cdot (-\sqrt2)^4=2\cdot 4=8


Если a=-√2, то значение выражения[tex] \frac{( - a {}^{3}) {}^{4} + ( - a {}^{4}) {}^{3} + ( - a {}^
Если a=-√2, то значение выражения[tex] \frac{( - a {}^{3}) {}^{4} + ( - a {}^{4}) {}^{3} + ( - a {}^
ПОКАЗАТЬ ОТВЕТЫ
Черничка21 Черничка21  03.10.2020 18:49